Guided by Evolution: Biology-Oriented Synthesis of Bioactive Compound Classes - Karageorgis, George; Waldmann, Herbert (Synthesis, 2019)
Biology-oriented-synthesis (BIOS), is a chemocentric approach to identifying structurally novel molecules as tools for chemical biology and medicinal chemistry research. The vast chemical space cannot be exhaustively covered by synthetic chemistry. Thus, methods which reveal biologically relevant portions of chemical space are of high value. Guided by structural conservation in the evolution of both proteins and natural products, BIOS classifies bioactive compound classes in a hierarchical manner based on molecular architecture and bioactivity. Biologically relevant scaffolds inspire and guide the synthesis of BIOS libraries, which calls for the development of suitable synthetic methodologies. These compound collections have enriched biological relevance, leading to the discovery of bioactive small molecules. These potent and selective modulators allow the study of complex biological pathways and may serve as starting points for drug discovery programs. Thus, BIOS can also be regarded as a hypothesis-generating tool, guiding the design and preparation of novel, bioactive molecular scaffolds. This review elaborates the principles of BIOS and highlights selected examples of their application, which have in turn created future opportunities for the expansion of BIOS and its combination with fragment-based compound discovery for the identification of biologically relevant small molecules with unprecedented molecular scaffolds.1 Introduction2 Structural Classification of Natural Products3 Implications and Opportunities for Biology-Oriented Synthesis4 Applications of Biology-Oriented Synthesis4.1 Chemical Structure and Bioactivity Guided Approaches4.2 Natural-Product-Derived Fragment-Based Approaches5 Conclusions and Outlook
Keywords: natural products; bioorganic chemistry; stereoselective synthesis; high-throughput screening; combinatorial chemistry